The degendering of male perpetrated intimate partner violence against female partners in Ontario family law courts. Issue 2 (3rd April 2021) - Morton, Mavis; Samardzic, Tanja; Cross, Pamela; Johnstone, Shannon; Vesely, Leslie; Choubak, Melisa
ABSTRACT: In this paper, we conducted a critical community-engaged Ontario family law case review of 46 cases from 2019 where intimate partner violence was identified. We explored the extent to which judges identified and addressed intimate partner violence and whether the gender of judges impacted on trial outcomes and judges' parental assessments. We found that judges de-gendered the language of violence, which impacted trial outcomes (e.g., more rulings of unsupervised access for fathers despite them having been violent) and a mutualisation of responsibility by referring to the violence as 'conflict.' We also found that male judges were more likely to negatively assess the mothers as both parents and witnesses. We call for more research that explores whether the changes to the Canadian federal Divorce Act (which includes 'family violence') will have an impact on the manner in which intimate partner violence is identified and/or referred to by family law judges, and if and how this influences the weighting of salient outcomes in Ontario family court cases.